2015
DOI: 10.1039/c5nj01114k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and optical and electrochemical properties of polycyclic aromatic compounds with S,S-dioxide benzothiophene fused seven rings

Abstract: ARTICLE This journal isA series of novel linearly-fused polycyclic aromatic compounds, N-(2-decyltetradecyl)carbazole bis [2,3b;6,7-b]benzo [d] thiophene-S,S-dioxide (CzBTO) and 9,9-dioctylfluorene bis[2,3-b;6,7b]benzo[d]thiophene-S,S-dioxide (FBTO), incorporating with S,S-dioxide benzothiophene unit were efficiently synthetized and detailedly characterized. The key step of preparing CzBTO and FBTO was related to the triflic acid induced intramolecular electrophilic cyclizing reaction where the corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…This quite low value of the LUMO level is similar to the values reported for extended carbazoles 28 , indenofluorenes 29 , triarylamine capped polyaromatic hydrocarbons 30 or others. 31 The consequence for such LUMO level, lying clearly below --2 eV, should be an easier electron injection from the cathode during the device operation.…”
Section: Resultssupporting
confidence: 68%
“…This quite low value of the LUMO level is similar to the values reported for extended carbazoles 28 , indenofluorenes 29 , triarylamine capped polyaromatic hydrocarbons 30 or others. 31 The consequence for such LUMO level, lying clearly below --2 eV, should be an easier electron injection from the cathode during the device operation.…”
Section: Resultssupporting
confidence: 68%
“…All of the desired compounds were readily obtained by one-pot Suzuki coupling reaction via using the commercially available N -phenyl-3-carbazolylboronic acid and 1,4-dibromo benzene derivatives directly. To promote the reaction yields and simplify the procedures of obtaining target compounds, the previous reaction systems of tetrabutylammonium bromide (TBAB), PdCl 2 , and the solvent of acetone were replaced by Pd(pph 3 ) 4 and toluene, respectively [ 29 , 30 ]. These improvements could successfully control the reaction to get the target products with high yields (>70%).…”
Section: Resultsmentioning
confidence: 99%
“…The ferrocene was used as a standard internal reference in this study, and the ferrocene/ferrocenium (Fc/Fc + ) redox shows a half-wave potential ( E 1/2 ) at 0.47 V. The CV curves are presented in Figure 4 , and the relative data are concluded in Table 3 . The highest occupied molecular orbital (HOMO) energy levels were calculated according to the empirical formula E HOMO = −e( E ox + 4.8 − E 1/2,(Fc/Fc + ) ) [ 30 ], where E ox is the onset of the oxidation potential. From Figure 4 , the E ox s are 0.97 eV, 1.31 eV, 1.13 eV and 0.91 eV for CzP-H, CzP-CN, CzP-Me and CzP-OMe, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that heteroatoms such as sulfur and nitrogen of HBTNI might avail to increase thermal stability and fluorescence quantum yield. [32] TPA and TPEF Coumarin 307 of 1 × 10 À 4 M in MeOH was selected as reference for δ calculations. [33] Both the SPEF parameters and the TPEF properties of compounds HTPI, HBTNI, HIPD, HPI, Fluorescein and Coumarin 307 were displayed in Table 1.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%